Efektivitas Model Cooperative Learning Team Games Tournament Berbantuan Media Ecopoly terhadap Hasil Belajar Kognitif Siswa Sekolah Dasar - Fatmasari, Lilis; Saskia, Arina Zahra; Sasongko, Dzikri Anjar Susilo; Ananti, Marsha Isnaini; Khaerani, Maryam; Safitri, Meiliani Intan; Alindra, Afridha Laily (STKIP HARAPAN BIMA, 2026)
This study was motivated by the importance of using appropriate instructional models and learning media to improve students’ learning outcomes in ecosystem topics. The purpose of this study was to analyze the effectiveness of the Cooperative Learning model of the Team Games Tournament (TGT) type assisted by Ecopoly game media in improving the cognitive learning outcomes of elementary school students. This study employed a One Group Pretest–Posttest design involving 24 fifth-grade students, consisting of 13 male and 11 female students. The instruments used were a test consisting of 10 items (5 multiple-choice questions and 5 essay questions) and documentation. Data were analyzed using a normality test, paired sample t-test, and N-Gain calculation. The results showed a significant difference between pretest and posttest scores (p 0.05), with an average N-Gain of 0.28, which falls into the low to moderate category. The highest achievement was found in the C1 (remembering) indicator, with an average posttest score of 86.95. These findings indicate that the TGT model assisted by Ecopoly media is effective in improving students’ cognitive learning outcomes, particularly in ecosystem material, in accordance with the cognitive developmental stage of elementary school-aged children.